Pengaruh Motivasi Belajar terhadap Prestasi Belajar Mata Pelajaran Fisika pada Siswa MTs Muhammadiyah 1 Singkawang Tahun Pelajaran 2024/2025 - Ramadan Ramadan; Andika Kusuma Wijaya; Haris Rosdianto (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to (1) determine the level of learning motivation among students at MTs Muhammadiyah 1 Singkawang, (2) identify the physics learning achievement of students at MTs Muhammadiyah 1 Singkawang, and (3) examine the influence of learning motivation on students’ physics learning achievement. The research employed a survey method with simple linear regression analysis, which is used to model the relationship between one dependent variable and one independent variable. The population consisted of all students at MTs Muhammadiyah 1 Singkawang, and the sampling technique applied was total sampling. Data were collected through a student learning motivation questionnaire and documentation of students’ physics grades.Descriptive analysis results indicated that the learning motivation variable had an average score of 85, which, based on the categorization criteria, falls into the very high category. In terms of physics learning achievement, data analysis revealed that the highest frequency was within the score interval of 30 < X ≤ 70. Specifically, 39 students (34%) were categorized as medium achievers, while 35 students (30%) were categorized as low achievers. These findings indicate that overall, students’ physics learning achievement can still be considered high, although a significant proportion remains in the medium and low categories.The results of simple linear regression analysis demonstrated a positive influence of learning motivation on physics learning achievement. This suggests that higher levels of learning motivation are associated with better physics performance among students. The findings highlight the importance of fostering and maintaining high learning motivation levels to enhance academic achievement. Therefore, educators are encouraged to design and implement learning strategies that not only improve students’ understanding of physics concepts but also stimulate and sustain their motivation to learn.